Weighted Fused Pathway Graphical Lasso for Joint Estimation of Multiple Gene Networks - Wu, Nuosi; Huang, Jiang; Zhang, Xiao-Fei; Ou-Yang, Le; He, Shan; Zhu, Zexuan; Xie, Weixin (Frontiers in Genetics, 2019)
Gene regulatory networks (GRNs) are often inferred based on Gaussian graphical models which could identify the conditional dependence among genes by estimating the corresponding precision matrix. Classical Gaussian graphical models are usually designed for single network estimation and ignore existing knowledge such as pathway information. Therefore, they can neither make use of the common information shared by multiple networks, nor can they utilize useful prior information to guide the estimation. In this paper, we propose a new Weighted Fused Pathway Graphical Lasso (WFPGL) to jointly estimate multiple networks by incorporating prior knowledge derived from known pathways and gene interactions. Based on the assumption that two genes are less likely to be connected if they do not participate together in any pathways, a pathway-based constraint is considered in our model. Moreover, we introduce a weighted fused lasso penalty in our model to take into account prior gene interaction data and common information shared by multiple networks. Our model is optimized based on the Alternating Direction Method of Multipliers (ADMM). Experiments on synthetic data demonstrate that our method outperforms other five state-of-the-art graphical models. We then apply our model to two real data sets. Hub genes in our identified stated-specific networks show some shared and specific patterns, which indicates the efficiency of our model in revealing the underlying mechanisms of complex diseases.